Advancements in Controlled Release Drug Delivery Systems for Fixed Dose Combinations: A Comprehensive Study - Acharya, Monika; Dubey, Gaurav (Journal of Neonatal Surgery, 2025)
Background: Controlled release drug delivery systems (CRDDS) and fixed-dose combinations (FDCs) have revolutionized pharmaceutical science, offering improved therapeutic outcomes and patient compliance. Integrating CRDDS into FDCs enables optimized drug release profiles, reduced dosing frequency, and enhanced medication synergy. Methods: This study evaluates key CRDDS techniques, including layered tablets, multiparticulate systems, matrix systems, and osmotic systems, focusing on their formulation, analytical approaches, and performance. Preformulation studies, coating techniques, dissolution testing, and stability studies were conducted to ensure quality and efficacy. Results: Layered tablets achieved multi-phased drug release with mechanical stability, while multiparticulate systems demonstrated flexible, individualized release profiles. Matrix systems provided sustained drug release through diffusion and erosion mechanisms, and osmotic systems exhibited pH-independent release over 24 hours. Analytical methods validated the compatibility, stability, and release profiles of formulations. Conclusions: CRDDS for FDCs offer significant benefits for managing complex diseases. Despite challenges in API compatibility, release kinetics, and regulatory requirements, advancements in materials, nanotechnology, and personalized medicine hold promise for innovative drug delivery solutions.